2018
DOI: 10.1007/s13205-018-1140-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome resequencing and transcriptomic analysis of genes regulating anthocyanin biosynthesis in black rice plants

Abstract: Anthocyanins are involved in many diverse functions in rice, but their benefits have yet to be clearly demonstrated. Our objective in this study was to identify anthocyanin-related genes in black rice plants. We identified anthocyanin-related genes in black rice plants using a combination of whole-genome resequencing, RNA-sequencing (RNA-seq), microarray experiments, and reverse-transcriptase polymerase chain reaction (RT-PCR). Using multi-layer screening from 30 rice accessions, we identified 172,922 single-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Differential transcriptomic analyses between pigmented and non-pigmented rice grains identified regulators and downstream targets of flavonoid pathway genes (Oh et al, 2018). The high anthocyanin content of black rice was associated with enhanced transcription of genes encoding anthocyanidin synthase, while high proanthocyanin content, characteristic of red rice, was accompanied by a notable abundance of transcript for a gene encoding leucoanthocyanidin reductase .…”
Section: 'Omics Approaches Taken To Unraveling the Mechanistic Basis mentioning
confidence: 99%
See 1 more Smart Citation
“…Differential transcriptomic analyses between pigmented and non-pigmented rice grains identified regulators and downstream targets of flavonoid pathway genes (Oh et al, 2018). The high anthocyanin content of black rice was associated with enhanced transcription of genes encoding anthocyanidin synthase, while high proanthocyanin content, characteristic of red rice, was accompanied by a notable abundance of transcript for a gene encoding leucoanthocyanidin reductase .…”
Section: 'Omics Approaches Taken To Unraveling the Mechanistic Basis mentioning
confidence: 99%
“…The application of 'omics-based platforms have begun to reveal the genetic and biochemical basis of the grain pigment parameters a * , b * , L * , hue, and chroma. While transcriptomic and metabolomic analyses have identified certain important structural and regulatory genes influencing core components of flavonoid synthesis Oh et al, 2018), what is still lacking is a comprehensive understanding of the molecular machinery underlying key metabolic processes such as the polymerization and transport of tannins. A more integrated approach, focusing on identifying linkages between regulatory networks is needed (Figure 2).…”
Section: 'Omics Approaches Taken To Unraveling the Mechanistic Basis mentioning
confidence: 99%
“…The reference-based transcriptome was performed on a total of four rice samples with two biological replicates each from both black rice as well as white rice [36]. The raw data generated were checked for the quality using FastQC and preprocessed, which include removing the adapter sequences and the low-quality bases (<q30).…”
Section: Illumina Sequencing Quality Control and Assemblymentioning
confidence: 99%
“…Anthocyanins, the end products of anthocyanin pathway, are ubiquitous pigments known to be present in flowering plants. Naturally occurring rice landraces that accumulate anthocyanins, proanthocyanins and anthocyanin derivatives have been widely described (Reddy et al , 1995; Oh et al , 2018). Historically, colored rices have been deemed specialty rices by various ancient Asian cultures.…”
Section: Introductionmentioning
confidence: 99%
“…It is an indica landrace cultivated in small restricted areas in farmer fields in southern India, often used as border lines to demarcate test plots in experimental fields, primarily serving as a pollen barrier due to its height (Rangaswamy et al , 1988). The genetic control of pericarp colour in PP has been described and molecular biological basis of the control of the underlying anthocyanin pathway has been elucidated (Reddy et al , 1994; Reddy et al , 1995; Reddy et al , 2007; Oh et al , 2018). Earlier studies on color in japonica rices revealed the contours of the genetic circuitry that govern color pathway (Furukawa et al , 2007).…”
Section: Introductionmentioning
confidence: 99%